Role of neurotransmitter receptors in behavioral disorders - A high-throughput analysis using text mining - Musa, Aliyu Kabir; Varo?lu, Ekrem; Taneri, Bahar (My University, 2011)
Allelic variation in neurotransmitter receptors have been shown to be implicated both in behavioural variations across individuals in a given population and in various behavioural disorders. There are two aspects of synaptic neurotransmission and its implications in behavioural disorders, both of which are important in healthcare management for such conditions. Firstly, certain allelic variations lead to an increased susceptibility to certain behavioural disorders. Secondly, specific allelic variations determine the response of affected individuals to available drug treatment options. These studies are in general done on molecular level and focused on single or a few disorders at a time. In this study, we aim to approach the relationship of neurotransmitter receptors to behavioural disorders from a different perspective. We employ state-of-the-art text mining methods to put together a comprehensive database linking receptors with specific disorders. This tool will enable researchers in the field to have easy access to a large amount of neurotransmission and disease data, and analyze these conditions within a larger scope. © 2011 IEEE.
6th International Symposium on Health Informatics and Bioinformatics, HIBIT 2011 --
Keywords: Allelic variation; Health-care managements; High-throughput analysis; Large amounts; Molecular levels; Text mining; Bioinformatics; Data mining; Drug therapy; Health care; Neurophysiology